Becoming a manager : how new managers master the challenges of leadership - Hill, Linda A. (Linda Annette), 1956- (Boston, Mass. : Harvard Business Press, 2003)
"In tracing and analyzing the experiences of nineteen new managers, Linda Hill reveals the profound complexity and difficulty of the process of developing into a manager. In their own distinct voices, these managers describe how they reframed their understanding of their roles and responsibilities and how they coped with the stresses and emotions of the transformation - in essence, how they were able to take on a new identity. Now, in an expanded second edition, the author offers concrete advice on the crucial issues of dealing effectively with organizational politics and developing and leading diverse teams in times of change, as well as on how managers can prepare themselves to lead over the course of their careers. In a new epilogue, she explores what organizations can do to help managers in their journey to lead and learn."--Jacket.
I. Learning what it means to be a manager. Setting the stage -- Reconciling expectations -- Moving toward a managerial identity -- II. Developing interpersonal judgment. Exercising authority -- Managing subordinates' performance -- III. Confronting the personal side of management. Gaining self-knowledge -- Coping with the stresses and emotions -- IV. Managing the transformation. Critical resources for the first year -- Easing the transformation -- V. Dispelling the myths of management. Exercising influence without formal authority -- Building an effective team -- Learning for a lifetime -- Epilogue: Creating a culture of leadership and learning.
Includes bibliographical references (pages 387-410) and index.
Online resource; title from PDF title page (EBSCO, viewed May 16, 2018).
Added to collection customer.56279.3
Keywords: Career changes; Management; Secondes carrières; Management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Career changes; Management; elektronické knihy; electronic books